PREDIKSI TOKSISITAS, ANALISIS ADME DAN DOCKING MOLEKULER ASIATICOSIDE TERHADAP PENGHAMBATAN ANGIOTENSIN CONVERTING ENZYME: TOXICITY PREDICTION, ADME ANALYSIS AND MOLECULAR DOCKING OF ASIATICOSIDE AGAINST ANGIOTENSIN CONVERTING ENZYME INHIBITION - Capritasari, Rafiastiana; Akrom, Akrom; Setianto, Arif Budi; Putri, Meilisa; Hasna, Elly Rosita; Astuti, Febriana (JFL : Jurnal Farmasi Lampung, 2025)
The presence of risk factors related to the severity of cardiovascular disease is a key consideration in adjunct therapy as an immunostimulant.One of the plants with potential as a cardioprotective immunostimulant is pegagan.Asiaticoside in pegagan leaves can inhibit AT1R and reduce NF-κβ activity.This study aims to predict the interaction of ligands with the receptor of cardioprotective immunostimulant agents.This study uses Molecular Docking simulations with molecular docking using Autodock Tools 1.5.6 and visualization using BIOVIA Discovery Studio Visualizer 24.1.The target macromolecule used is AT1R (PDB 4ZUD) which was downloaded from the PDB.The molecular docking parameters were analyzed based on binding energy.Pharmacokinetic characteristics were evaluated using the SwissADME tool.The binding result of the test ligand molecule to AT1R is -4.50 ±0.595 kcal/mol. The reference ligand has an AT1R binding value of -7.74±0.036 kcal/mol. Validation of the molecular docking method has an RMSD value of 1.857±0.356 Å. The toxicity prediction of the compound Asiatikoside at LD50 4000mg/kg and pharmacokinetic analysis were conducted using the boiled-egg method, which indicates that  Asiatikoside is predicted cannot cross the blood-brain barrier. The ADME prediction results show that the Asiatikoside has 3 parameters that do not meet the bioavailability parameters, namely a molecular weight of 959.12g/mol, TPSA polarity of 315.21A, and flexibility of 10. Conclusion Asiaticosides is predicted to have limitations in terms of oral bioavailability, so special formulations such as nanoencapsulation techniques are needed to help improve its bioavailability Keywords:  Asiaticosides; ACE Inhibition; Molecular Docking